Sun’s procedure for complex aortic arch repair: total arch replacement using a tetrafurcate graft with stented elephant trunk implantation - Ma, Wei-Guo; Zhu, Jun-Ming; Zheng, Jun; Liu, Yong-Min; Ziganshin, Bulat A.; Elefteriades, John A.; Sun, Li-Zhong (Annals of Cardiothoracic Surgery; Vol 2, No 5 (September 01, 2013): Frozen Elephant Trunk, 2013)
The Sun's procedure is a surgical technique proposed by Dr. Li-Zhong Sun in 2002 that integrates total aortic arch replacement using a tetrafurcated graft with implantation of a specially designed frozen elephant trunk (Cronus®) in the descending aorta. It is used as a treatment option for extensive aortic dissections or aneurysms involving the ascending aorta, aortic arch and the descending aorta. The technical essentials of Sun's procedure include implantation of the special open stented graft into the descending aorta, total arch replacement with a 4-branched vascular graft, right axillary artery cannulation, selective antegrade cerebral perfusion for brain protection, moderate hypothermic circulatory arrest at 25 ℃, a special anastomotic sequence for aortic reconstruction (i.e., proximal descending aorta → left carotid artery → ascending aorta → left subclavian artery → innominate artery), and early rewarming and reperfusion after distal anastomosis to minimize cerebral and cardiac ischemia. The core advantage of Sun's procedure lies in the use of a unique stented graft, which has superior technical simplicity, flexibility, inherent mechanical durability and an extra centimeter of attached regular vascular graft at both ends. Since its introduction in 2003, the Sun's procedure has produced satisfactory early and long-term results in over 8,000 patients in China and more than 200 patients in South American countries. In a series of 1,092 patients, the authors have achieved an in-hospital mortality rate of 6.27% (7.98% in emergent or urgent vs. 3.98% in elective cases). Given the accumulating clinical experience and the consequent, continual evolution of surgical indications, the Sun's procedure is becoming increasingly applied/used worldwide as an innovative and imaginative enhancement of surgical options for the dissected (or aneurysmal) ascending aorta, aortic arch and proximal descending aorta, and may become the next standard treatment for type A aortic dissections requiring repair of the aortic arch.